2008
DOI: 10.1097/mph.0b013e318162c476
|View full text |Cite
|
Sign up to set email alerts
|

A Community-based Physical Activity Program for Adolescents With Cancer (Project TREK)

Abstract: Adolescents with a history of cancer are undoubtedly susceptible to the same maladaptive health habits as are their healthy peers. Innovative interventions aimed at improving their adherence to positive behavioral interventions, such as PA are warranted. Although not without limitations, this study provides preliminary data in support of a university-sponsored PA intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
213
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(227 citation statements)
references
References 40 publications
10
213
1
3
Order By: Relevance
“…69 However, a recent community-based intervention showed improvements in QOL in adolescents surviving cancer. 43 In contrast, the intrahospital intervention of San Juan et al 71 showed no effect on QOL. As with other outcomes, limited supervision interventions, such as that of Takken et al 47 , did not show any improvement in fatigue.…”
Section: Adultsmentioning
confidence: 66%
See 3 more Smart Citations
“…69 However, a recent community-based intervention showed improvements in QOL in adolescents surviving cancer. 43 In contrast, the intrahospital intervention of San Juan et al 71 showed no effect on QOL. As with other outcomes, limited supervision interventions, such as that of Takken et al 47 , did not show any improvement in fatigue.…”
Section: Adultsmentioning
confidence: 66%
“…A recent community-based intervention showed improvements in physical activity levels and physical fitness in adolescents surviving cancer, though they returned to low physical activity levels shortly after they finished the program. 43 Intrahospital, individually supervised training programs also appear beneficial for young ALL survivors. San Juan et al 71 reported that a 16-week combined aerobic and resistance training intervention of thrice weekly activity for 90-120 min significantly improved aerobic fitness in very young (4-7 years) pediatric ALL survivors in maintenance treatment phase.…”
Section: Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the numerous LAE related to pediatric cancer treatment, an interest in using exercise as a therapeutic measure to attenuate or reverse many cancer-related LAE in the pediatric population has surfaced. While comparatively less studied, the research suggests that there is a positive effect of physical activity on organ system function, fatigue, and physical well-being in children during and after cancer treatment [39][40][41][42][43][44][45][46][47][48][49]. It is clear that children who exercise can increase aerobic fitness and strength, with the latter a result of neuromuscular adaptations rather than skeletal muscle hypertrophy.…”
Section: Introductionmentioning
confidence: 99%